Status from fighting? Reassessing the relationship between conflict involvement and diplomatic rank. Issue 2 (3rd March 2020) - Ward, Steven
ABSTRACT: Recent research has provided evidence that conflict improves a belligerent's status. I argue that this finding is based on a specification error. The relationship between the CINC index, which is used to control for material capabilities as a potential confounder, and change in diplomatic rank is not linear. Accounting for this non-linearity eliminates the apparent positive effect of MID initiation on change in diplomatic rank, and also reduces the effect of MID victory. The analysis has significant implications for foreign policy, for ongoing debates over the most useful way to model the link between status dissatisfaction and belligerence, and, more broadly, for analyses that use CINC to control for material capabilities.